Deciphering the Controversial Role of TP53 Inducible Glycolysis and Apoptosis Regulator (TIGAR) in Cancer Metabolism as a Potential Therapeutic Strategy - Fatima I. AlMaazmi; Lara J. Bou Malhab; Leen ElDohaji; Maha Saber-Ayad (Cells)
Tumor metabolism has emerged as a critical target in cancer therapy, revolutionizing our understanding of how cancer cells grow, survive, and respond to treatment. Historically, cancer research focused on genetic mutations driving tumorigenesis, but in recent decades, metabolic reprogramming has been recognized as a hallmark of cancer. The TP53 inducible glycolysis and apoptosis regulator, or TIGAR, affects a wide range of cellular and molecular processes and plays a key role in cancer cell metabolism by regulating the balance between glycolysis and antioxidant defense mechanisms. Cancer cells often exhibit a shift towards aerobic glycolysis (the Warburg effect), which allows rapid energy production and gives rise to biosynthetic intermediates for proliferation. By inhibiting glycolysis, TIGAR can reduce the proliferation rate of cancer cells, particularly in early-stage tumors or specific tissue types. This metabolic shift may limit the resources available for rapid cell division, thereby exerting a tumor-suppressive effect. However, this metabolic shift also leads to increased levels of reactive oxygen species (ROS), which can damage the cell if not properly managed. TIGAR helps protect cancer cells from excessive ROS by promoting the pentose phosphate pathway (PPP), which generates NADPH—a key molecule involved in antioxidant defense. Through its actions, TIGAR decreases the glycolytic flux while increasing the diversion of glucose-6-phosphate into the PPP. This reduces ROS levels and supports biosynthesis and cell survival by maintaining the balance of nucleotides and lipids. The role of TIGAR has been emerging as a prognostic and potential therapeutic target in different types of cancers. This review highlights the role of TIGAR in different types of cancer, evaluating its potential role as a diagnostic marker and a therapeutic target.